2016
DOI: 10.1080/09168451.2015.1079478
|View full text |Cite
|
Sign up to set email alerts
|

A thiostrepton resistance gene and its mutants serve as selectable markers inGeobacillus kaustophilusHTA426

Abstract: Effective utilization of microbes often requires complex genetic modification using multiple antibiotic resistance markers. Because a few markers have been used in Geobacillus spp., the present study was designed to identify a new marker for these thermophiles. We explored antibiotic resistance genes functional in Geobacillus kaustophilus HTA426 and identified a thiostrepton resistance gene (tsr) effective at 50 °C. The tsr gene was further used to generate the mutant tsr(H258Y) functional at 55 °C. Higher fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Streptomyces azureus ATCC 14921 is categorized in the blue-spore Streptomyces cyaneus cluster and is known to be a thiostrepton producer ( 4 ). The thiostrepton resistance gene ( tsr ), which is a selective marker often used in the genetic engineering of actinomycetes, was isolated from the strain ( 5 , 6 ). S. azureus contains the pock-forming conjugative plasmid pSA1.1 ( 7 ), and spontaneous development of pocks in the strain is caused by the action of the plasmid and lysogenic phage SAt2 ( 8 ).…”
Section: Genome Announcementmentioning
confidence: 99%
“…Streptomyces azureus ATCC 14921 is categorized in the blue-spore Streptomyces cyaneus cluster and is known to be a thiostrepton producer ( 4 ). The thiostrepton resistance gene ( tsr ), which is a selective marker often used in the genetic engineering of actinomycetes, was isolated from the strain ( 5 , 6 ). S. azureus contains the pock-forming conjugative plasmid pSA1.1 ( 7 ), and spontaneous development of pocks in the strain is caused by the action of the plasmid and lysogenic phage SAt2 ( 8 ).…”
Section: Genome Announcementmentioning
confidence: 99%
“…In addition, Wada et al (2016) also demonstrated tsr as a viable selection marker for the thermophilic Geobacillus kaustophilus besides demonstrating accurate selection as a single copy in Streptomyces strains.…”
Section: Introductionmentioning
confidence: 94%
“…Mycobacteria are naturally resistant to many antibiotics and requires use of stable drugs with low frequency of spontaneous resistance for selection, hence limiting the alternative choices (Parish and Brown, 2008). The combined use of multiple markers enables more versatile genetic modifications, including the stable maintenance of multiple plasmids and inactivation of multiple genes (Wada et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Genetic tools are available for this strain [10][11][12][13][14][15][16]. The whole genome sequence has been determined [17], showing that G. kaustophilus HTA426 harbors the circular plasmid pHTA426 (Figure 1).…”
Section: Archaea -New Biocatalysts Novel Pharmaceuticals and Variousmentioning
confidence: 99%